Influence of Azadirachta indica and Cnidoscolus angustidens aqueous extract on cattle ruminal gas production and degradability in vitro - Elghandour, Mona M. M. Y.; Acosta-Lozano, Néstor; Alvarado, Tonantzin Díaz; Castillo-Lopez, Ezequias; Cipriano-Salazar, Moises; Barros-Rodríguez, Marcos; Inyang, Udoh Akpan; Purba, Rayudika Aprilia Patindra; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2023)
Introduction Mitigation of ruminant greenhouse gas (GHG) emissions is crucial for more appropriate livestock production. Thus, there is a need of further research evaluating feed supplementation strategies to mitigate enteric GHG emissions and other gases produced within the rumen. Methods This study was conducted as a completely randomized experimental design to determine the effectiveness of liquid extracts from A. indica (AZI), C. angustidens (CNA), or their combination (Mix. 1:1) at dosages of 0, 36, 72, and 108 mg of liquid extract/g DM substrate incubated in reducing GHG production in vitro, particularly methane (CH4), from the diet of steers during anaerobic incubation in rumen fluid. Total gas production, CH4, CO, H2S, and fermentative characteristics were all measured in vitro. Results Treatment AZI at a dose of 108 mg of liquid extract/g DM substrate produced the highest (P < 0.05) gas volume at 6 h, whereas CNA at a dose of 72 mg of liquid extract/ g DM substrate produced the least (P < 0.05) at 6 and 24 h, and Mix. at a dose of 72 mg of liquid extract/g DM substrate produced the least (P < 0.05) at 48 h. In addition, CH4 levels at 6 and 24 h of incubation (36 mg/g DM substrate) were highest (P < 0.05) for CNA, and lowest (P < 0.05) for AZI, whereas this variable was lowest (P < 0.05) at 72 mg of liquid extract for CNA at 24 and 48 h. At 6 and 24 h, CO volume was highest (P < 0.05) for AZI at 108 mg of liquid extract and lowest (P < 0.05) for Mix. at 72 mg of liquid extract. Treatment Mix. had a high (P < 0.05) concentration of short chain fatty acids at 72 mg of liquid extract/g DM of substrate. Discussion In general, herbaceous perennial plants, such as AZI and CNA, could be considered suitable for mitigating enteric GHG emissions from animals. Specifically, the treatment Mix. achieved a greater sustainable reduction of 67.6% in CH4 and 47.5% in H2S production when compared to either AZI. This reduction in CH4 might suggest the potential of the combination of both plant extracts for mitigating the production of GHG from ruminants.